To find the inverse you have steps
1. replace f(x) with y
2. swich x and y places
3. solve for y
4. replace y with f⁻¹(x) (read 'f inverse')
so we have
f(x)=2x+1
replace f(x) with y
y=2x+1
switch x and y
x=2y+1
solve for y
x=2y+1
subtract 1
x-1=2y
divide both sides by 2
![\frac{x-1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx-1%7D%7B2%7D%20)
=y
y=
![\frac{x-1}{2}](https://tex.z-dn.net/?f=%20%5Cfrac%7Bx-1%7D%7B2%7D%20)
repplace y with f⁻¹(x)
f⁻¹(x)=
It equals 1.7 because you're moving the decimal point by two places, when dividing by 100
6/12 or 1/2 I hope this was the right answer and helped you
The answer to this question is 3,3